Implementation of Adaptive Neuro-Fuzzy Inference System and Image Processing for Design Applications Paper Age Prediction - Valeria Cynthia Dewi; Victor Amrizal; Fenty Eka Muzayyana Agustin (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2023)
The development of technology today is widely misused by some people who intend to forge paper on documents and books. One way to find out the authenticity of a paper is by knowing its age. The age of paper can be known in several ways: carbon dating, uranium dating, and potassium-argon dating. But these methods still have weaknesses, requiring sophisticated equipment at a high cost, long processes to get results and limited access. To solve this problem, researchers made an application that can identify the age range of a sheet of paper with a faster process, low cost and does not have to be used by laboratory employees alone. The application is a Paper Age Prediction Application made desktop-based, using the MATLAB programming language with the Anfis Sugeno (TSK) Gaussian membership function method. Image processing by taking the average values of C, M, Y, and K from 70 images used as a database and will be trained with ANFIS. The research method uses interviews, observations, and literature studies—the prototype application development method. The test results showed an application success rate in identifying 60 data that had been trained by 100% against 40 that had not been trained by 42.5%.